Treating the “E” in “G × E”: Trauma-Informed Approaches and Psychological Therapy Interventions in Psychosis - Gianfrancesco, Olympia; Bubb, Vivien J.; Quinn, John P. (Frontiers in Psychiatry, 2019)
Despite advances in genetic research, causal variants affecting risk for schizophrenia remain poorly characterised, and the top 108 loci identified through genome-wide association studies (GWAS) explain only 3.4% of variance in risk profiles. Such work is defining the highly complex nature of this condition, with omnigenic models of schizophrenia suggesting that gene regulatory networks are sufficiently interconnected such that altered expression of any ‘peripheral’ gene in a relevant cell type has the capacity to indirectly modulate the expression of ‘core’ schizophrenia-associated genes. This wealth of associated genes with small effect sizes makes identifying new druggable targets difficult, and current pharmacological treatments for schizophrenia can involve serious side effects. However, that the majority of schizophrenia genome-wide associated variants fall within non-coding DNA suggests their potential to modulate gene regulation. This would be consistent with risk that can be mediated in a ‘gene x environment’ (G x E) manner. Stress and trauma can alter the regulation of key brain-related pathways over the lifetime of an individual, including modulation of brain development and neurochemistry in the adult. Recent studies demonstrate a significant overlap between psychotic symptoms and trauma, ranging from prior trauma contributing to psychosis, as well as trauma in response to the experience of psychosis itself or in response to treatment. Given the known effects of trauma on both CNS gene expression and severity of psychosis symptoms, it may be that pharmacological treatment alone risks leaving individuals with a highly stressful and unresolved environmental component that continues to act in a ‘G x E’ manner, with the likelihood that this would negatively impact recovery and relapse risk. This review aims to cover the recent advances elucidating the complex genetic architecture of schizophrenia, as well as the long-term effects of early life trauma on brain function and future mental health risk. Further, the evidence demonstrating the role of ongoing responses to trauma or heightened stress sensitivity, and their impact on the course of illness and recovery, is presented. Finally, the need for trauma-informed approaches and psychological therapy-based interventions is discussed, and a brief overview of the evidence to determine their utility is presented.